Intentional Collaboration With Speech-Language Pathologists to Support Language Outcomes of Students With Emotional and Behavioral Disorders. (December 2022) - Chow, Jason C.; Morse, Ashley; Senter, Reed
This article argues for intentional collaboration between teachers of students with emotional and behavioral disorders and speech-language pathologists. After providing a rationale, we detail how special education teachers can leverage the expertise of speech-language pathologists during the Individualized Education Program process. We provide actionable steps that special education teachers and speech-language pathologists can take together to improve the identification, assessment, and subsequent support of language difficulty in students with emotional and behavioral disorders.